Pelatihan Keterampilan Penggunaan Microsoft Word Pada SISWA SMA Islamiyah Weru Lor - Furqon, Muhammad; Siti Aisha Nurcita; Putri Camelia; Putri Diah Pramesti; Aris Riyanto; Muhammad Furqon (LPPM POLITEKNIK LP3I, 2024)
Mastering digital technology, particularly the ability to use Microsoft Word software, is a highly important skill for students in this digital era (Hasibuan, 2024). Therefore, Microsoft Word training at SMA Islamiyah Weru Lor is considered essential to enhance students' proficiency in using this software. The training program is carried out in several stages, namely preparation, implementation, and evaluation. During the preparation stage, training needs were identified and relevant materials were developed. The training was conducted in person with an approach that combines theory and practice, where students were taught how to use various Microsoft Word features, including mail merge. To evaluate the training results, questionnaires were distributed to students to assess the improvement in their skills after the training. The evaluation results showed that the average score obtained by students in the questionnaires was 3.77 out of 5, which falls into the